An Interpretive Account of Counsellor Development - Chang, Jeff (Canadian Journal of Counselling and Psychotherapy, 2011)
Using a hermeneutic approach to inquiry, the author interviewed 8 counsellors in training to gain an understanding of the question, “How do counsellors in training develop, and how do they make sense of what they are doing/what is happening to them?” Their accounts were integrated into a single emerging story that captures their experience and the meaning they attached to their counsellor education experiences. Organized temporally, this story of counsellor development was divided into four phases: foreshadowings, opening chapters, denouement, and final chapter (conclusions). Finally, implications for counsellor education practice are discussed.